Co-evaluation: effective strategy to promote metacognition in writing - Ramírez Seminario, Fabiola de Fátima (2024)
The competency-based approach is committed to a student capable of managing their own learning in different fields of knowledge. In this context, metacognition plays an important role that has allowed a better performance of the student in his academic and professional life; and even personal. One of the fields in which this higher-order thinking skill has been successfully applied, through various strategies, is in text writing. Therefore, the immediate objective of this research is to develop metacognitive skills in writing in higher level students based on the co-evaluation or peer evaluation strategy. In this way, the autonomy of the student is enhanced, since he is able to reflect on his cognitive processes, when writing academic texts, and self-regulate them. This study is of a quasi-experimental type and was applied to a sample of 68 students of a language course at a private university. The results allow us to determine that co-evaluation significantly promotes the skills that make up metacognition in the production of texts.